The existence of minimizers of energy for diffeomorphisms between two-dimensional annuli in R2 and R3. (April 2022) - Kalaj, David; Zhu, Jian-Feng
Abstract: In this paper, we consider the minimization for the Dirichlet energy of Sobolev homeomorphisms between two-dimensional annuli in R 2 and R 3, respectively. It should be noticed that in this case a Nitsche phenomenon occurs. The main result of this paper partly extends the corresponding result in Astala et al. (2010).